Exploring the Narratives and Agency of Children with Migrant Backgrounds within Schools Researching Hybrid Integration - Baraldi, Claudio (Migration and Education, 2023)
This edited volume presents the results of a European research project - 'CHILD-UP' (Children Hybrid Integration: Learning Dialogue as a way of Upgrading Policies of Participation), which analyses the hybrid integration of children with migration backgrounds into schools across Europe. Using qualitative data and theoretical foundations obtained through interviews and focus groups, the book ultimately centres the perspectives and experiences of both the children and the professionals working with them. In doing so, it explores the complex position migrant children occupy in host societies, their exercise of agency, challenges and inspirational local practices that support hybrid integration and innovative educational planning. It also analyses the facilitation of conversations concerning children's personal experiences and social relations, second language learning and language mediation, based on video- and audio-recordings of school activities. The book will be of relevance to researchers, academics, scholars, and faculty in the fields of sociology of education, child development, migration and multicultural studies. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.